Exploring the intersection of machine learning and explainable artificial intelligence: An analysis and validation of ML models through XAI for intrusion detection - Rahman, Masroor; Navid, Reshad Karim; Hossain Bhuyain, Md Muballigh; Hasan, Farnaz Fawad; Nup, Naima Ahmed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.